2019
DOI: 10.22159/ajpcr.2019.v12i7.33627
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry PREPARATION OF DIFFERENT CRUDE EXTRACT AND ANTIMICROBIAL STUDIES OF SPIROGYRA RHIZOPUS

Abstract: Objective: The importance of this work is to prepare the crude extracts of Spirogyra rhizopus and to study the biological activity of crude extract against four bacterial strains. Materials and Methods: Spirogyra algae collected from Jimma town, and crude extracts were prepared by cold percolation method and sonication method and further analyzed for qualitative phytochemical analysis. The efficacy of crude extracts is tested for bacterial activity by disc-diffusion method. Results: The maximum zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…The studies tested the antibiotic effect of the ethanol, chloroform, petroleum ether, methanol, and acetone extracts from Spirogyra spp. against several bacteria like P. solanacearum, E. coli, and C. michiganens, showed a highly significant antibiotic activity against P. solanacearum (Naik et al, 2012;Dwaish et al, 2016;Daniel et al, 2019). Similarly, this study demonstrated a high zone of inhibition (19 mm) against Gram-positive S. aureus when the ethanol extract (Usharani et al, 2015).…”
Section: Discussionmentioning
confidence: 61%
“…The studies tested the antibiotic effect of the ethanol, chloroform, petroleum ether, methanol, and acetone extracts from Spirogyra spp. against several bacteria like P. solanacearum, E. coli, and C. michiganens, showed a highly significant antibiotic activity against P. solanacearum (Naik et al, 2012;Dwaish et al, 2016;Daniel et al, 2019). Similarly, this study demonstrated a high zone of inhibition (19 mm) against Gram-positive S. aureus when the ethanol extract (Usharani et al, 2015).…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies by Dwaish et al 2016;Syamsuddin et al 2016;Uthorn et al (2019) This observation is consistent with a prior study indicating that Spirogyra rhizopus, extracted using various solvents such as ethanol, methanol, chloroform, and acetone, exhibited substantial inhibitory efficacy against S. typhimurium, P. aeruginosa, S. aureus and E. coli. (Daniel et al 2019). Methanol extracts demonstrated the highest zone of inhibition against all strains except for S. lutrae, S. lugdunensis and E. coli, where ethanol had the most potent inhibitory effect.…”
Section: Discussionmentioning
confidence: 88%
“…It has been reported that both Hexadecanoic acid and Octadecadienoic acid demonstrate antibacterial activity, inhibiting Grampositive and Gram-negative bacteria to some extent. (Kumar et al 2015;Dwaish et al 2016;Okunowo et al 2017;Daniel et al 2019). Hence, it can be inferred that Phytol 9,12-Octadecadienoic acid ethyl ester and Hexadecanoic acid possess potent antimicrobial properties.…”
Section: Discussionmentioning
confidence: 99%